2008
DOI: 10.1159/000158663
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Study of Cell Growth Inhibition of Simvastatin on Chronic Myelogenous Leukemia Cells

Abstract: Background: Statins, a family of 3-hydroxy-3-methylglutaryl CoA (HMG CoA) reductase inhibitors, are being investigated for the therapy and prevention of cancers. Here we aimed to investigate the effects of simvastatin on chronic myelogenous leukemia (CML) cells in vitro and in vivo, and to elucidate the mechanisms. Methods: Cell proliferation and cell cycle were measured after K562 cells were incubated with simvastatin, and differentially expressed genes were determined by oligonucleotide microarray. Changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…In vitro and in vivo studies showed that statins inhibit tumor cell growth, induce apoptosis, inhibit angiogenesis and impair the metastatic process (16). Although simvastatin has been demonstrated to modulate the pathogenesis of many cancer types by inhibiting tumor cell growth dynamics, data on simvastatin induced effects on hepatocellular carcinoma are sparse (11,17,18). The present in vitro model reveals that simvastatin significantly influenced both the cell growth and adhesion behaviour of human hepatocellular carcinoma cells HepG2 and Huh7.…”
Section: Discussionmentioning
confidence: 88%
“…In vitro and in vivo studies showed that statins inhibit tumor cell growth, induce apoptosis, inhibit angiogenesis and impair the metastatic process (16). Although simvastatin has been demonstrated to modulate the pathogenesis of many cancer types by inhibiting tumor cell growth dynamics, data on simvastatin induced effects on hepatocellular carcinoma are sparse (11,17,18). The present in vitro model reveals that simvastatin significantly influenced both the cell growth and adhesion behaviour of human hepatocellular carcinoma cells HepG2 and Huh7.…”
Section: Discussionmentioning
confidence: 88%
“…In CML cells, it has been reported that simvastatin or a combination of lovastatin and interferon-alpha 2b led to cell growth inhibition through cell cycle arrest and caused significant reduction of phosphorylation in tyrosine, serine and threonine protein residues. 43,44 As such, inhibition of cholesterol synthesis, for example by statins, is a potential adjunct to CML therapy. It would be curious to examine whether the encouraging response rates reported in human AML trials combining standard chemotherapy with statins 45 are associated with lipid raft disruption and blockade of CXCR4 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA expression may be used as a marker of cell proliferation because cells the G1/S phase may be extended when proliferating. In addition, PCNA is essential in nucleic acid metabolism as a component of the DNA replication and repair mechanism (33,34). P53 is an anti-oncogene, and its downregulation or deletion is associated with tumor proliferation and antioncogene inactivation.…”
Section: Discussionmentioning
confidence: 99%